Postprandial Bioassay and Radical Scavenging on n-Hexane Fraction of Cordia myxa L. Leaf - Virsa Handayani; Aktsar Roskiana Ahmad; Nur Rezky Khairun Nisaa; La Hamidu; Ahmad Najib (Faculty of Pharmacy, Universitas Muslim Indonesia, 2022)
Cordia myxa L. is empirically used as an antidiabetic medication. The aim of this study is to determine the in-vivo effect of Cordia myxa L. n-hexane fraction on reducing blood sugar levels and their relationship with the anti-free-radical activity assay using DPPH (1,1-diphenyl-2-Picrylhydrazyl). The n-hexane fraction of Cordia myxa L. was used as a sample in the post-prandial assay which was analyzed using the ANOVA statistical test followed by Post-Hoc test. The results showed that there were significant in the extract using a 500 mg dose. In the anti-free-radical test using DPPH (1,1-diphenyl-2-Picrylhydrazyl) at maximum wavelength of 516 nm, 16.49 µg /mL IC50 value was obtained. For comparison, Quercetin with IC50 0.13 µg/mL was used. This shows that the sample has strong anti-free radical inhibitory potential ranged from 10 µg/mL to 50 µg/mL. The data from the calculation showed that there is a correlation between its effect of lowering high blood sugar level and anti-free radical activity